Sistem Pendukung Keputusan Bagi Penerima Bantuan Siswa Miskin (BSM) Menggunakan Metode Simple Additive Weighting (SAW) di SMA Negeri 1 Raren Batuah Kabupaten Barito Timur - Ebet Tri Cahyanu; Siska Dewi Lestari; Herry Hermawan (Journal of Applied Informatics and Computing, 2019)
Raren Batuah 1 High School is a senior high school education level located at Unsum Village, Raren Batuah District, East Barito Regency, at Raren Batuah 1 High School, assistance is provided in the form of subsidies for Poor Student Assistance for the smooth teaching and learning process for students less fortunate. To help the selection process for recipients of Poor Student Assistance, a decision support system has been designed using the Simple Additive Weighting (SAW) method by prioritizing the criteria of parental income, the number of dependents of parents, and the value of student report cards that will be used for a reference decision making for the right recipient of Poor Student Assistance. Decision Support System Application (DSS) for Poor Student Assistance Recipients was designed using Flowchart and implemented using the Microsoft Visual Basic.Net 2010 programming language.